Reef fish assemblages and feeding guild communities in relation to depth, reef profile and substrate cover at Tunku Abdul Rahman Park, Kota Kinabalu, Sabah - Nur Farhana Azmi (2022)
Understanding reef fish ecology and its dynamic interaction with its habitats plays a crucial role in manifesting effective marine park management strategies as well as navigating insights of possible problems. This thesis investigated the spatial distribution of reef fish assemblage, feeding guild and substrate composition across the two most influential environmental gradients in marine habitat, depth, and reef profile. Underwater visual census (UVC) combined with baited remote underwater station (BRUVS) surveys between 5-20 m found that depth and reef profile play significant roles in influencing reef fish assemblage, however, both factors fail to show interaction as co-factors. Depth was found to significantly affect fish species richness in which greater species richness was observed at shallower depths whereas reef profile significantly affected reef fish abundance where it was observed to be greater at slope profile. Multitudes of different individual species responses were recorded on 24 representative species, in which 13 showed significant interaction with depth and/or profile while other species remained ambiguous. Composition of feeding guild communities were found to be significantly dissimilar between depths in which higher abundance of roving carnivores was recorded at 20 m. An order of magnitude of more snappers and ten times more groupers were sampled at deeper depths, thus raising some evidence for “depth refuge hypothesis”. Higher abundance of planktivores at the reef slope and higher abundance of omnivores at the reef shelf drive dissimilarities of feeding guild composition between reef profiles. Substrate composition changed significantly across depth and profile, however, showed relatively low correlation with patterns of reef fish assemblage and feeding guild composition. This thesis describes the dynamic interaction of reef fish assemblage across environmental gradients within its habitat and highlights the importance of understanding this ecological interaction to create better strategies in marine resource management.